2021
DOI: 10.1021/acs.jctc.1c00412
|View full text |Cite
|
Sign up to set email alerts
|

Natural Charge-Transfer Analysis: Eliminating Spurious Charge-Transfer States in Time-Dependent Density Functional Theory via Diabatization, with Application to Projection-Based Embedding

Abstract: For many types of vertical excitation energies, linear-response time-dependent density functional theory (LR-TDDFT) offers a useful degree of accuracy combined with unrivaled computational efficiency, although charge-transfer excitation energies are often systematically and dramatically underestimated, especially for large systems and those that contain explicit solvent. As a result, low-energy electronic spectra of solution-phase chromophores often contain tens to hundreds of spurious charge-transfer states, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 158 publications
1
12
0
Order By: Relevance
“…The use of LRC functionals in aqueous-phase TD-DFT calculations is necessary to avoid contamination of the spectrum by a plethora of spurious, low-energy charge-transfer states. The presence of such states adds considerably to the cost of the calculation but can also impact line shapes, via spurious intensity borrowing . Functionals such as BH&HLYP with a larger-than-normal fraction of exact exchange have also been used to address this problem, but they tend to overestimate valence excitation energies, pushing them closer to Hartree–Fock values that are typically overestimated by 0.8 eV or more .…”
supporting
confidence: 70%
“…The use of LRC functionals in aqueous-phase TD-DFT calculations is necessary to avoid contamination of the spectrum by a plethora of spurious, low-energy charge-transfer states. The presence of such states adds considerably to the cost of the calculation but can also impact line shapes, via spurious intensity borrowing . Functionals such as BH&HLYP with a larger-than-normal fraction of exact exchange have also been used to address this problem, but they tend to overestimate valence excitation energies, pushing them closer to Hartree–Fock values that are typically overestimated by 0.8 eV or more .…”
supporting
confidence: 70%
“…Recently, Herbert and co-workers have used PbE in combination with TDDFT for the determination of the excited state in solution including selective solvent molecules by determining an effective CT acceptor space by projection . Significantly contributing solvent molecules within this subspace are then included in the active subsystem in the subsequent PbE-sTDDFT calculation.…”
mentioning
confidence: 99%
“…(The GDD-tuned values of ω for each of the systems considered in this work can be found in Tables S1–S8 of the Supporting Information.) Previous work has shown that tuned values of ω are sensitive to the fraction of short-range exact exchange, but for a given density functional, these values are rather insensitive to the choice of basis set . The SG-1 quadrature grid is used for LRC-ωPBE.…”
Section: Computational Detailsmentioning
confidence: 99%